Determinants of Hand Hygiene Compliance and Practice Among Nurses from West-coast Malaysia - Noor Hasliza, Che Seman; Juhary, Ali; Soon, Lean Keng (2025)
Introduction: The Centers for Disease Control and Prevention emphasizes hand hygiene as crucial for reducing infection transmission in healthcare, yet its importance is underrecognized, and compliance rates are low. Objective: The study was conducted to assess self-reported hand hygiene compliance and practice among nurses in Malaysia. Methods: A cross-sectional study was conducted on 388 nurses randomly selected in four Malaysian hospitals using a structured, self-administered questionnaire. Measures were taken for convergent validity, concept, reliability, and content. The study used numerical data analysis to assess nurses’ self-reported hand-hygiene compliance and practices. Histograms were used to examine data normality, and post-hoc tests were conducted using the Games-Howell test after confirming the assumptions. Simple and multiple linear regression was used to identify associated factors with self-reported hand-hygiene compliance and practice. Results: The study found male nurses outperformed female nurses in terms of hand-hygiene practice and compliance scores, with the former having a nursing degree or diploma qualification. The hand-hygiene compliance score of male Indian nurses with degrees was the highest; however, Chinese nurses with degrees had a 12.36 times higher likelihood of scoring on the hand-hygiene practice scale. Conclusion: Male nurses with degrees and diplomas outperformed females in self-reported hand-hygiene compliance and practice scores, with both male and female Indian and Chinese nurses scoring higher than Malay and ‘other race’ nurses. A quality improvement project is needed to identify the root causes of hand hygiene compliance issues and identify areas for improvement.